Epigenetic modulation of vascular calcification: Looking for comprehending the role of sirt1 and histone acetylation in VSMC phenotypic transition - Feltran, Geórgia da Silva [UNESP]; Alves dos Santos, Emerson Araújo [UNESP]; de Camargo Andrade, Amanda Fantini [UNESP]; Zambuzzi, Willian Fernando [UNESP]; da Silva, Rodrigo Augusto Foganholi (Elsevier, 2024)
In light of the complex origins of ectopic vascular calcification and its significant health implications, this study offers a comprehensive exploration of the molecular dynamics governing vascular smooth muscle cells (VSMCs). Focusing on epigenetic modulation, we investigate the transition from a contractile to a calcifying phenotype in VSMCs, with an emphasis on understanding the role of SIRT1. For this purpose, a single batch of human aortic SMCs, used at a specified passage number to maintain consistency, was subjected to calcium and phosphate overload for up to 72 h. Our findings, validated through RT q-PCR, Western blot, immunofluorescence, and DNA methylation analyses, reveal a complex interplay between acetyltransferases and deacetylases during this phenotypic transition. We highlight HAT1A's critical role in histone acetylation regulation and the involvement of HDACs, as evidenced by subcellular localization studies. Moreover, we demonstrate the modulation of SIRT1 expression, a class III deacetylase, during VSMC calcification, underscoring the influence of DNA methylation in this process. Importantly, the study addresses previously unexplored aspects of the dynamic protein expression patterns observed, providing insight into the counterintuitive expressions of key proteins such as Runx2 and osterix. This research underscores the significant impact of epigenetic mechanisms, particularly the modulation of SIRT1, in the transition from a contractile to a calcifying phenotype in VSMCs, offering potential avenues for further exploration in the context of vascular calcification.
Keywords: Epigenetic regulation; Histone acetylation; SIRT1; Vascular calcification; Vascular smooth muscle cells (VSMCs)